Stevens Johnson Syndrome: Past, Present, and Future Directions Gynecologic Manifestations and Management in SJS/TEN - DenAdel, Michelle A.; Hendrickson, Sarah E.; Fuchs, Esther (Frontiers in Medicine, 2022)
Acute manifestations of Stevens Johnson Syndrome (SJS) and Toxic Epidermal Necrolysis (TEN) often include vulvovaginal erosions and ulcerations that can lead to adhesions, vaginal stenosis, dryness, pain, dyspareunia, bleeding, and adenosis. Protocols largely rely on expert opinion and little data exists on the efficacy of suggested management. The goal of this review was to identify the impact of a clinical care pathway on treatment of vulvovaginal SJS/TEN. Methods: We performed a retrospective chart review of females with SJS/TEN at our institution from 2008 to 2021. Data collected from the electronic medical record were compared before and after implementation of a protocol in 2017. Results: We reviewed 88 charts, included 77 females and identified 42 patients (55%) with vulvovaginal involvement. 2008-2017 (pre-protocol), 55 patients identified, 53% (n=29) had vulvovaginal involvement (n=26 vulvar, n=21 vaginal). Gynecology was consulted in 26% (n=14), recommendations for dilator use, vulvar treatment and menstrual suppression were inconsistent. 2017-2021 (post-protocol), 22 patients identified, 72% (n=16) had vulvovaginal involvement (n=16 vulvar, n=9 vaginal). Gynecology consultations increased from 26% pre-, to 86% post-protocol, and for patients with vulvovaginal involvement even from 50% to 93%. Dilator use with topical steroid ointment, menstrual suppression and antifungals were consistently recommended. Conclusion: A protocol increases the consistency of gynecologic consultation, the documentation and treatment of vulvovaginal SJS/TEN. We need to improve clinical follow-up after discharge from the hospital and obtain long-term data on quality of life and sexual functioning. The role of local estrogen, vaginal laser and pelvic floor physical therapy needs further exploration.